Heartsblood : - Petersen, David (Island Press/Shearwater Books, 2000)
Petersen, a hunter and outdoorsman, offers a personal, carefully considered exploration of hunting, drawing on a great deal of literature in the field, including biological, philosophical, spiritual, political, and particularly ethical perspectives on hunters and hunting.